Contribution of autophagy‐related gene 5 variants to acquired aplastic anemia in Han‐Chinese population. Issue 7 (14th February 2019) - You, Yahong; Huo, Jiali; Huang, Jinbo; Wang, Min; Shao, Yingqi; Ge, Meili; Li, Xingxin; Huang, Zhendong; Zhang, Jing; Nie, Neng; Zheng, Yizhou
Abstract: Immune‐mediated quantitative and qualitative defects of hematopoietic stem/progenitor cells (HSPCs) play a vital role in the pathophysiology of acquired aplastic anemia (AA). Autophagy is closely related to T cell pathophysiology and the destiny of HSPCs, in which autophagy‐related gene 5 (ATG5) is indispensably involved. We hypothesized that genetic variants of ATG5 might contribute to AA. We studied six ATG5 polymorphisms in a Chinese cohort of 176 patients with AA to compare with 157 healthy controls. A markedly decreased risk of AA in the recessive models of rs510432 and rs803360 polymorphisms (adjusted odds ratio [OR], 95% confidence interval [CI] = 0.467 [0.236‐0.924], P  = 0.029 for ATG5 rs510432; adjusted OR [95% CI] = 0.499 [0.255‐0.975], P  = 0.042 for ATG5 rs803360) was observed. Furthermore, the decreased risk was even more pronounced among nonsevere AA compared with healthy controls under recessive models (adjusted OR [95% CI] = 0.356 [0.141‐0.901], P  = 0.029 for ATG5 rs510432; adjusted OR [95% CI] = 0.348 [0.138‐0.878], P  = 0.025 for ATG5 rs803360; adjusted OR [95% CI] = 0.352 [0.139‐0.891], P  = 0.027 for ATG5 rs473543). Above all, rs573775 can strongly predict the occurrence of newly onset hematological event in patients with AA. Our results indicate that genetic ATG5 variants contributed to AA, which may facilitate further clarifying the underlying mechanisms of AA and making a patient‐tailored medical decision. Abstract : Acquired aplastic anemia (AA) is an autoimmune‐mediated organ‐targeted disease, and, autophagy‐related gene 5 (ATG5) is involved in many diseases. we found that ATG5 variants were significantly associated with susceptibility of AA, and besides, rs573775 of ATG5 can predict the occurrence of new hematological events which can help make a better treatment decision.